2013
DOI: 10.1002/stem.1302
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Regulation of Nanog by MiR-302 Cluster-MBD2 Completes Induced Pluripotent Stem Cell Reprogramming

Abstract: While most somatic cells undergoing induced pluripotent stem (iPS) cell reprogramming with Yamanaka factors accumulate at stable partially reprogrammed stages, the molecular mechanisms required to achieve full reprogramming are unknown. MicroRNAs (miRNAs) fine-tune mRNA translation and are implicated in reprogramming, but miRNA functional targets critical for complete iPS cell reprogramming remain elusive. We identified methyl-DNA binding domain protein 2 (MBD2) as an epigenetic suppressor, blocking full repro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
70
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(73 citation statements)
references
References 47 publications
3
70
0
Order By: Relevance
“…Accordingly, the Wrana lab divided the reprogramming of MEFs into three phases termed Initiation, Maturation and Stabilization, based on gene expression profiling, and reported MET as a hallmark of the Initiation phase between days 0 and 5 post-transduction (Samavarchi-Tehrani et al, 2010). Following up on these findings, several groups have identified microRNAs (Lee et al, 2013;Wang et al, 2013;Liao et al, 2011b;Li et al, 2011), genes (Chen et al, 2012;Takahashi et al, 2014;Sakurai et al, 2014) and epigenetic modifiers (Hu et al, 2014;Onder et al, 2012;Liang et al, 2012) which enhance reprogramming by promoting MET, either directly by stimulating the expression of epithelial proteins, or indirectly by inhibiting EMT inducing signals. Thus, extensive research on cell signaling and gene regulation points towards an important, and potentially causal, link between cell epithelialization and gain of pluripotent characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the Wrana lab divided the reprogramming of MEFs into three phases termed Initiation, Maturation and Stabilization, based on gene expression profiling, and reported MET as a hallmark of the Initiation phase between days 0 and 5 post-transduction (Samavarchi-Tehrani et al, 2010). Following up on these findings, several groups have identified microRNAs (Lee et al, 2013;Wang et al, 2013;Liao et al, 2011b;Li et al, 2011), genes (Chen et al, 2012;Takahashi et al, 2014;Sakurai et al, 2014) and epigenetic modifiers (Hu et al, 2014;Onder et al, 2012;Liang et al, 2012) which enhance reprogramming by promoting MET, either directly by stimulating the expression of epithelial proteins, or indirectly by inhibiting EMT inducing signals. Thus, extensive research on cell signaling and gene regulation points towards an important, and potentially causal, link between cell epithelialization and gain of pluripotent characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…53 Also, a recent investigation suggests overexpression of miR-302 enhances the pluripotent marker, Nanog, hence increases the generation of iPSC by suppressing methyl-DNA-binding domain protein 2 (MBD2). 54 On the other hand, the inhibition of the let-7 miRNA family, with a negative role in the maintenance of ESC the method of transcription factor-mediated reprogramming. [46][47][48] Meanwhile, the introduction of certain proto-oncogene can result in oncogenesis, which hurdles the path to clinical application.…”
mentioning
confidence: 99%
“…It will be important to overcome the difficulty of reprogram cancer cells. Application of other factors in addition to the Yamanaka factors may be effective, such as exogenous expression of miRNA-302, chemical compound such as histone deacetylate inhibitor, and knock down of p53, p21, and Ink4/Arf [14]. We used Sendai virus system, which is efficient induction of transgene free iPSCs.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro clonogenic growth upon serial re-plating, secondary colony formations were significantly inhibited by hedgehog pathway inhibitors. These results suggested that the hedgehog inhibitors may become extremely useful therapeutic interventions in a number of hematological neoplasms, including MDS, where the persistence of cancer stem cells [13,14].…”
Section: Introductionmentioning
confidence: 98%